Medical Students’ Perception Regarding E- Learning during Covid-19 Lockdown Period - Manandhar, Pratibha; Manandhar, Naresh; Joshi, Sunil Kumar (Journal of College of Medical Sciences-Nepal, 2021)
Background and Objectives: Due to Covid-19 lockdown period undergraduate medical institutions across the country are moving towards e-learning for continuity of education. The purpose of this study is to determine the perceptions of students towards e-learning and to analyze medical students’ perception on e-learning vs. conventional learning. Materials and Method: This was a descriptive cross sectional study conducted by distributing an online semi-structured questionnaire consisting Likert scale to undergraduate medical students of Kathmandu Medical College. Data assembled from the survey were analyzed and Statistical package for social sciences (SPSS) 24 version software was used for data analysis. Result: A total of 273 students were enrolled in this study. Most of the students, 83.9% (229) had the perception that conventional teaching method was the best method for learning as compared to e-learning method 16.1% (44). The students mentioned that conventional method of learning is more effective to increase knowledge than e -learning (M= 3.87, M= 2.80) which was statistically significant (p=0.000). Conclusion: E-learning was the only option for students to study during lockdown period. But students preferred conventional method of learning as compared to e-learning. It might be due to some disadvantages of e-learning, eg. Technical difficulties, lack of interaction with teacher and patients, etc. So, these measures have to be addressed for improving e-learning for betterment of teaching-learning activity during these types of circumstances in future.